Envelopes addressed to Max Bredig, 1937 - Zadek, Liselotte; Boas, Fritz (1937)
Two envelopes addressed to Max Albert Bredig (1902-1977), sent from Lisolotte Zadek and Fritz Boas.
Keywords: Bredig, Max Albert, 1902-1977; Zadek, Liselotte; Boas, Fritz; Envelopes (Stationery)